Role of Serum Creatinine Phosphokinase in Outcome Prediction of Intoxicated Patients; a Brief Report - Dadpour, Bita; Tajoddini, Shahrad; Shaarbaf Eidgahi, Elham; Shokouhizadeh, Mohsen; Shafahi, Azam (Archives of Academic Emergency Medicine, 2017)
Introduction: Several mechanisms were introduced as causes of serum creatinine phosphokinase (CPK) raise in intoxicated patients. This study aimed to assess the relationship between serum CPK level in the first 24 hours and baseline characteristics as well as outcomes of these patients. Methods: This one year retrospective cross-sectional study was conducted on all intoxicated patients, who were admitted to a referral toxicology center, Northwest of Iran, stayed for at least 24 hours and had serum CPK level more than 500 IU/L in the first 24 hours of admission. The relationship between serum CPK level and some baseline and outcome variables were studied using SPSS version 21. Results: 413 patients with the mean age of 34.52 ± 15.24 years were studied (78.7% male). The mean CPK level at the time of presentation to ED was 3702.85 ± 6375.29 IU/L. There was not any significant relationship between presenting CPK level and type of poisoning (p = 0.258), sex (p = 0.587), and age (p = 0.817). The area under the ROC curve of CPK in prediction of need for dialysis, need for intensive care unit (ICU) admission, and mortality was 0.67 (95% CI: 0.57 – 0.77), 0.60 (95% CI: 0.52 – 0.69), and 0.60 (95% CI: 0.51 – 0.68), respectively. Conclusion: Based on the finding of present study, there was no significant association between serum CPK level in the first 24 hours and age, sex, and type of poisoning of intoxicated patients and it had poor accuracy in prediction of their need to do dialysis, need for ICU admission, and mortality.